Directed evolution of feruloyl esterase from Lactobacillus acidophilus and its application for ferulic acid production. (July 2021) - Liu, Shujun; Soomro, Lubna; Wei, Xue; Yuan, Xufeng; Gu, Tianyi; Li, Zhen; Wang, Yulu; Bao, Yuming; Wang, Fengzhong; Wen, Boting; Xin, Fengjiao
Highlights: The homogeneous dimer of FAELac achieved 37-fold higher activity. Site-directed mutagenesis enlarged the substrate-binding pocket. The catalytic activities of five mutants were enhanced. Different enzymes had specific adaptability of natural substrates. A high yield of ferulic acid (6.60 mg/g substrate) was obtained by mutant Q134T. Abstract: Producing ferulic acid (FA) from the natural substrate with feruloyl esterase is promising in industries, screening and engineering new enzymes with high efficiency to increase the FA yield is of great concern. Here, the feruloyl esterase of Lactobacillus acidophilus (FAELac) was heterologous expressed and the FAELac with different oligomerization states was separated. Interestingly, the activity of dimer was 37-fold higher than high-polymer. To further enhance the efficiency of FAELac, eight mutants were generated based on the simulated structure, of which Q198A, Q134T enhanced the catalytic efficiency by 5.4- and 4.3-fold in comparison with the wild type. Moreover, higher yields of FA (2.21, 6.60, and 1.67 mg/g substrate, respectively) were released by the mutants from de-starched wheat bran, insoluble wheat arabinoxylan, and steam-exploded corn stover. These results indicated that improving the purification process, engineering new FAELac and substrates bias studies hold great potential for increasing FA production yield.